Multicentre retrospective study of 97 cases of intraoral lipoma - Perez‐Sayáns, Mario; Blanco‐Carrión, Andrés; Oliveira‐Alves, Monica G.; Almeida, Janete Dias; Anbinder, Ana Lia; Lafuente‐Ibáñez de Mendoza, Irene; Aguirre‐Urízar, José Manuel (Journal of oral pathology & medicine, 2019)
Background Lipomas are benign neoplasms derived from adipose tissue that are unfrequently found in the oral cavity. The objective of this study is to identify the main clinicopathological characteristics of this tumour in a case series of oral lipomas (OL) in a population from Spain and Brazil. Material and Methods A multicentre retrospective observational study was conducted in collaboration with the Oral Pathology Unit of the São Paulo State University (UNESP), São José dos Campos, in Brazil, and the Oral Medicine and Pathology Units of the University of Santiago de Compostela (USC) and the University of the Basque Country (UPV/EHU) in Spain. Results This multicentre series consists of a total of 97 of OL cases, 31 (32%) of which correspond to Spain, and 66 (68%) to Brazil with an overall prevalence of 0.33%. The average age of the patients is 56.44 years old, with a range of 10‐92 (SD = 15.52). Buccal mucosa was the most frequent location (42.3%). Cases from Spain coexisted with other lesions in a significant number of cases, 12.9%, vs Brazil, 1.5% (P = 0.018). According to the progression time, Brazil has an average of 60.35 months (CI: 27.20‐93.51), compared to 5.41 months in Spain (CI: 3.17‐7.65) (P = 0.022). Average size is 12.55 mm (SD = 11.06), ranging from 2 to 75 mm. A positive correlation is also seen between the increase in the lesion size and a greater progression time (CC = 0.367; P = 0.008). Conclusions Correct differential diagnosis of the clinical lesion is key, followed by a good histopathological study, to achieve the final diagnosis.